Open Innovation Framework on Industrial Sector in Baja California, Mexico - Ponce Camacho, Miguel Ángel; López-Leyva, Josué Aarón (Association for Computing Machinery, New York, NY, United States, 2021)
Considering the Mexican govemment funding policy and historical results on Research, Innovation and Development in the 2009-2017 period, the open innovation framework is analyzed for the industrial sector of Baja California state as an important facet of regional industrial development. As a first approach, through public information about innovation initiatives in global enterprises established in Mexicali, Tijuana and Ensenada cities; open innovation key activities are identifed. These innovation actions are based on important national support for industrial innovation in the region. As a result, the financial contribution of the government sector increased considerably, the link between the industrial and academic sectors was strengthened, and different methodologies and best practices applications related to industrial innovation increased as part of the added value and competitiveness in industrial processes. RESUMEN Considerando la política de financiamiento del gobierno mexicano y los resultados históricos en Investigación, Innovación y Desarrollo en el período 2009-2017, se analiza el marco de innovación abierta para el sector industrial del estado de Baja California como una faceta importante del desarrollo industrial regional. Como primera aproximación, a través de información pública sobre iniciativas de innovación en empresas globales establecidas en las ciudades de Mexicali, Tijuana y Ensenada; Se identifican actividades clave de innovación abierta. Estas acciones de innovación se basan en un importante apoyo nacional a la innovación industrial en la región. Como resultado, se incrementó considerablemente el aporte financiero del sector gobierno, se fortaleció el vínculo entre el sector industrial y el académico, y se incrementó la aplicación de diferentes metodologías y mejores prácticas relacionadas con la innovación industrial como parte del valor agregado y la competitividad en los procesos industriales.
ICEBA 2021: 2021 7th International Conference on E-Business and Applications
Keywords: open innovation; multinational enterprise; industril & academic collaboration; Sistema